Changes in Adolescent Fertility in Benin From 2006 to 2017 (London Journal of Medical and Health Research, 2023)
Due to over social control and social representative of sex, adolescents adopt risky behavior exposing them to early pregnancies. This study aims to analyze fertility factors among adolescents in Benin. It uses data sets from 2007, 2014 and 2017 Demographic and Health Surveys (DHS) to describe adolescents’ behavior feeding early fertility status. On top of logistic model, simple and advanced decomposition analysis are used to determine the sources of change in adolescent fertility over the study period. The results highlight that adolescent’s age, first cohabitation with opposite sex and first sexual intercourse have the greatest impact in adolescent’s fertility. The sources of phenomenon changes within the 10 years are rooted in household standard of living and adolescent level of education. These changes are either linked with individual behavior or related to government measures. To reduce early pregnancy among adolescents, individual and collective solutions are requested. Firstly, sex education for adolescents must focus on modern contraception methods, early pregnancy risks and postponement of the first sexual intercourse. Secondly, raising community awareness to mitigate cultural patterns which tend to expose teenagers to pregnancy, to law age of first cohabitation, and early marriage.
Keywords: adolescent; fertility; SDGS; sexual and reproductive health; behavior change communication